Genomic insights into the complex demographic history and inbreeding phenomena during Zhou Dynasty on the Central Plains of China - Wu, Xiyan; Ding, Baoxu; Nie, Linyi; Zhong, Canshuo; Liu, Pengxiang; Liang, Jingteng; Wang, Lin; Gao, Xiangping; Wei, Jiyin; Zhou, Yawei (Frontiers in Microbiology, 2024)
In the Central Plains of China during the Zhou Dynasty (1046-256 BCE), the social hierarchy gradually solidified, accompanied by frequent wars and the phenomena of multicultural and multi-ethnic integration. These social phenomena collectively influenced the population's genetic structure at that time. However, our understanding of the genetic history of this period remains largely unknown owing to limited ancient DNA studies. In this study, we successfully obtained 11 ancient genomes from the Guanzhuang site during the Zhou Dynasty on the central plain of China. Our findings revealed remarkable genetic continuity with the Neolithic populations of the Yellow River Basin and emphasized genetic diversity through the analysis of uniparental genetic markers. Population structure analysis further confirmed the genetic similarity between the Guanzhuang population and ancient populations of the Yellow River Basin and indicated genetic exchanges with ancient populations from surrounding regions. Intriguingly, signs of inbreeding within the Guanzhuang community cast doubt on the stringent enforcement of the contemporary marital regulations against consanguineous marriages within the same surname or clan. These revelations significantly enhance our insight into the complex interplay of ancient demography and societal organization, concurrently presenting a genetic perspective to view the complex evolution of Chinese civilization's multiethnic.